Dose–Response Effect of Vibratory Stimulus on Synaptic and Muscle Plasticity in a Middle-Aged Murine Model - Cariati, Ida; Bonanni, Roberto; Annino, Giuseppe; Scimeca, Manuel; Bonanno, Elena; D’Arcangelo, Giovanna; Tancredi, Virginia (Frontiers in Physiology, 2021)
Whole Body Vibration plays a central role in many work categories and can represent a health risk to the musculoskeletal system and peripheral nervous system. However, studies in animal and human models have shown that vibratory training, experimentally and/or therapeutically induced, can exert beneficial effects on the whole body, as well as improve brain functioning and reduce cognitive decline related to the aging process. Since the effects of vibratory training depend on several factors, such as vibration frequency and vibration exposure time, in this work we investigated whether the application of three different vibratory protocols could modulate synaptic and muscle plasticity in a middle-aged murine model, counteracting the onset of early symptoms linked to the aging process. To this end, we performed in vitro electrophysiological recordings of the field potential in the CA1 region of mouse hippocampal slices, as well as histomorphometric and ultrastructural analysis of muscle tissue by optic and transmission electron microscopy, respectively. Our results showed that protocols characterised by a low vibration frequency and/or a longer recovery time exert positive effects at both hippocampal and muscular level, and that these effects are optimal by varying both parameters, with an action comparable to a dose-response effect. Thus, we suggested that vibratory training may be an effective strategy to counteract cognitive impairment, which is already present in the early stages of the aging process, and the onset of sarcopenia, which is closely related to a sedentary lifestyle. Future studies will be needed to understand the underlying molecular mechanisms and to determine an optimal vibratory training protocol.